Deepwater response in the African cultivated rice Oryza glaberrima. (2nd January 2023) - Luo, Quanshu; Sasayama, Daisuke; Nakazawa, Misaki; Hatanaka, Tomoko; Fukayama, Hiroshi; Azuma, Tetsushi
ABSTRACT: Partial submergence of Oryza sativa deepwater rice elicits enhancement of internodal elongation, referred to as deepwater response, conferred by three types of genes, SNORKEL1/2 ( SK1/2 ), SEMIDWARF1 ( SD1 ), and ACCELERATOR OF INTERNODE ELONGATION 1 ( ACE1 ). We investigated the presence and expression of these genes in the African cultivated rice Oryza glaberrima and the relationship between these genes and the deepwater response of O. glaberrima . In 49 of the 50 accessions tested, one or two SK genes were identified, which could be divided into three types of SK1 and four types of SK2 . The accessions with the SK2 type whose expression was induced by submergence demonstrated rapid internodal elongation under submergence. In most of these accessions, submergence also increased the expression of SD1 and ACE1 genes. However, the accessions did not possess the haplotype of SD1 that is associated with high deepwater response in O. sativa . In contrast, they possessed the type of ACE1 gene similar to that in O. sativa deepwater rice. These results indicate that the molecular mechanisms underlying induction of deepwater response in O. glaberrima are similar to that found in deepwater rice of O. sativa and suggest that most O. glaberrima cultivars, including upland cultivars, can exhibit rapid internodal elongation under submergence. GRAPHICAL ABSTRACT: uf0001